Potassium perchlorate only temporarily restores euthyroidism in patients with amiodarone-induced hypothyroidism who continue amiodarone therapy - Bogazzi, F.; Bartalena, L.; Tomisti, L.; Dell’Unto, E.; Cosci, C.; Sardella, C.; Tanda, M. L.; Lai, A.; Gasperi, M.; Aghini-Lombardi, F.; Martino, E. (Journal of endocrinological investigation, 2008)
Context : Amiodarone-induced hypothyroidism (AIH) may occur in patients with or without underlying thyroid disorders. In the latter, restoration of euthyroidism, after amiodarone discontinuation, can be facilitated and accelerated by a short course of potassium perchlorate (KClO 4 ). However, it is unknown whether KClO 4 may exert similar effects on thyroid function of AIH patients if amiodarone treatment is continued. Objective : To evaluate the effects of KClO 4 on thyroid function in AIH patients (without underlying thyroid disease) while continuing amiodarone treatment. Design and patients : An open, prospective study of 10 consecutive AIH patients without underlying thyroid abnormalities referred to a tertiary referral center, and treated with KClO 4 (600 mg/day) for a period of 26±13 days (range, 15–45 days). An additional, historical group of 12 consecutive patients with subclinical AIH left untreated while continuing or after withdrawing amiodarone was retrospectively evaluated as to the outcome of thyroid function. Measurement : Serum free T 4 , free T 3 , and TSH concentrations were measured at booking, during KClO 4 treatment and after withdrawing the drug. Results : In the prospective study, KClO 4 treatment restored euthyroidism in all patients within 28±11 days (range, 15–45 days). After KClO 4 with drawal, however, all patients became hypothyroid again after 45±15 days (range, 30–60 days). Two patients developed mild leukopenia (1 case) or a slight increase in serum creatinine levels (1 case), which promptly normalized after KClO 4 withdrawal. In the historical group, followed for at least 12 months, euthyroidism was spontaneously and stably achieved after an average of 6 months in 5 patients in whom amiodarone could be discontinued, while subclinical hypothyroidism persisted in 7 patients in whom amiodarone had to be continued. Conclusions : KClO 4 very effectively restores normal thyroid function in AIH patients without underlying thyroid abnormalities, despite the fact that amiodarone therapy is continued. However, euthyroidism does not persist after KClO 4 is withdrawn; in addition, spontaneous recovery of euthyroidism does not seem to occur in this subset of AIH patients, unless amiodarone is discontinued. Therefore, also in view of its potential side-effects, KClO 4 cannot be recommended as a first-line treatment for AIH if amiodarone needs to be continued, while LT 4 replacement is recommended under these circumstances, with periodical reassessment of thyroid function.